2022
DOI: 10.4049/jimmunol.2200141
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptional Mechanisms Governing Innate-like T Lymphocyte Development

Abstract: Innate-like lymphocytes are a subset of lymphoid cells that function as a first line of defense against microbial infection. These cells are activated by proinflammatory cytokines or broadly expressed receptors and are able to rapidly perform their effector functions owing to a uniquely primed chromatin state that is acquired as a part of their developmental program. These cells function in many organs to protect against disease, but they release cytokines and cytotoxic mediators that can also lead to severe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…To this end, one might need to isolate DNA/RNA and protein for downstream applications such as real-time PCR to evaluate expression of specific genes (Gioulbasani et al, 2020;Pereira et al, 2014) or to perform multiomic analysis such as RNA-seq to evaluate gene expression, ATAC-seq to evaluate chromatin accessibility, whole-genome bisulfite sequencing to assess DNA methylation, or CMS-IP sequencing to assess distribution of 5-hydroxymethylcytosine (Aijo et al, 2022;Engel et al, 2016;Theofilatos et al, 2022;Tsagaratou et al, 2017). Collectively, the past few years' integrative analyses of multiomic approaches have shed light on the transcriptional and epigenetic regulation of iNKT cells (Morgan & Kee, 2022). For the above experiments, it is critical to identify iNKT cell subsets while maintaining the cells alive.…”
Section: Identifying Inkt Cell Subsets Based On Surface Marker Expres...mentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, one might need to isolate DNA/RNA and protein for downstream applications such as real-time PCR to evaluate expression of specific genes (Gioulbasani et al, 2020;Pereira et al, 2014) or to perform multiomic analysis such as RNA-seq to evaluate gene expression, ATAC-seq to evaluate chromatin accessibility, whole-genome bisulfite sequencing to assess DNA methylation, or CMS-IP sequencing to assess distribution of 5-hydroxymethylcytosine (Aijo et al, 2022;Engel et al, 2016;Theofilatos et al, 2022;Tsagaratou et al, 2017). Collectively, the past few years' integrative analyses of multiomic approaches have shed light on the transcriptional and epigenetic regulation of iNKT cells (Morgan & Kee, 2022). For the above experiments, it is critical to identify iNKT cell subsets while maintaining the cells alive.…”
Section: Identifying Inkt Cell Subsets Based On Surface Marker Expres...mentioning
confidence: 99%
“…It is critical to focus on specific subsets in order to decipher the unique features that define them. Research in the last decade has shed light on distinct transcriptional and epigenetic principles that govern the development of each subset (Harsha Krovi et al., 2020; Morgan & Kee, 2022; Verykokakis & Kee, 2018). iNKT subsets are transcriptionally and epigenetically heterogeneous, with varying regulation leading to their distinct effector functions (Engel et al., 2016).…”
Section: Commentarymentioning
confidence: 99%
“…This specific binding towards DNA sequences could inhibit transcription by recruiting co-repressors via its amino terminal POZ domain. However, PLZF is also able to stimulate transcription depending on the activator and suppressor [35,93]. According to previous studies, PLZF was found to be involved in diverse signaling as well as differentiation and growth-regulatory pathways [58].…”
Section: Plzfmentioning
confidence: 99%
“…Innate/innate-like effector lymphocytes are quick responders; they can act as quickly as cells of innate immune system or faster [reviewed in refs ( 21 , 22 )]. This feature in several innate/innate-like effector lymphocytes is ingrained during development by a genome regulatory network under the control of a promyelocytic leukemia zinc finger transcription factor (encoded by Zbtb16 ; reviewed in ref ( 35 , 36 )]. Activated innate/innate-like effector lymphocytes secrete a wide variety of cytokines and chemokines with which they can steer downstream type I, II, and III immune responses ( Figure 2 ).…”
Section: Introduction: ‘For a Secret Offence A Secret Revenge’mentioning
confidence: 99%